EDUKASI PEMANFAATAN BUAH NAGA MERAH SEBAGAI BAHAN DISCLOSING AGENT PADA MASYARAKAT SRENGAT, BLITAR - Dea Cahyani, Yessica; Khafid, Mohammad; Handajani, Juni; Hanindriyo, Lisdrianto; Irnawati, Dyah; Susilowati, Heni; Sunarintyas, Siti (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Using a disclosing agent to control plaque is one way to improve dental health and oral tissue. However, this material is not widely known to the public. Red dragon fruit, a mainstay commodity in Blitar Regency, contains betalain which can be used as an alternative disclosure agent. Therefore, the people of Blitar Regency need to be empowered to maintain dental and oral health regarding the potential of dragon fruit as an alternative natural ingredient. The aim is to provide education regarding the potential benefits of dragon fruit as a disclosure agent. The strategy used in this activity is dual media intervention by dentists, namely by using interactive lectures with PowerPoint media and booklet media to community groups in, Blitar Regency. To measure the level of knowledge of the target community, questionnaires were given before and after the activity, as well as checking the OHI-S index. The research results showed that the level of the OHI-S index was in the medium category, while the level of community knowledge showed an increase of 56.78% after being given counseling. This shows that providing dental and oral health education using PowerPoint media and booklet media has proven to be effective in increasing public knowledge. Therefore, it can be concluded that providing education on the use of red dragon fruit as a disclosing agent to the people of Blitar Regency has proven effective in increasing knowledge, so it is hoped that it can improve the community's dental and oral hygiene.